The in vitro digestibility study of fecal and feed sample of white rhinoceros - Abd. Latif, Muhammad Husaini (2017)
As a non-ruminant herbivore, the white rhinoceros has the ability to utilize fibrous plant matter through microbial fermentation in the hindgut. This study was conducted to determine the fermentation ability in the hindgut fermenter which is white rhinoceros and compared to foregut fermenter which is the cattle. As for treatment for this study, the rhinoceros feed provided by Zoo Negara and Napier grass were used as feed sample. The rhinoceros feed was produced from the mixture of hay and concentrate. The total gas production from faecal and rumen inoculum were compared from the feed samples used. Proximate analysis were conducted in order to know the nutritive value of hay, concentrate and Napier grass. For the concentrate sample, the nutrient composition were 5.43% of dry matter (DM), 8.26% of ash (OM), 14.64% of crude protein (CP) and 46.51% of neutral detergent fibre (NDF). For the hay sample, the nutrient composition are 10.08% of dry matter (DM), 6.73% of ash (OM), 17.27% of crude protein (CP) and 45.49% of neutral detergent fibre (NDF). Lastly, for the Napier grass feed sample, the nutrient composition were 9.6% of dry matter (DM), 10.40% of ash (OM), 10.66% of crude protein (CP) and 72.25% of neutral detergent fibre (NDF).